Les quatre éléments dans « Karain » de Joseph Conrad : du mythe au manque - Catherine Delmas (Cahiers Victoriens et Edouardiens)
The East and West dichotomy in “Karain” is in keeping with the romantic topos and underlined by the motif of the four elements. The vision of the sea, the sky and the island builds up an orientalist painting full of colours and light, and turns the Malay Archipelago into a mythic space to be opposed to the dreary and foggy representation of the West, an enclosed, corrupt and oppressive space paradoxically paralysed by economic and technological progress at the end of the Victorian era. However Conrad subverts the opposition by casting light on the illusion and artificiality of the representation and deconstructing the orientalist myth. The four elements first highlight the motif of human illusions and contribute to the symbolic function of the East ; they also serve a literary topos by enhancing the tragic muthos which is then immediately deconstucted ; the orientalist mode of representation is also called into question by impressionism, conveyed by fragmentation and the relativity of the point of view. The aestheticization of space in the orientalist painting clearly shows the decoy of representation and lets the reader have a glimpse of the reality of colonialism through the cracks of the painting. The four elements are subservient to Conrad’s imaginary vision, whose purpose was to make his reader hear, feel, and see the truth “below the surface of the visible universe” (The Nigger of the Narcissus), “disclosed in a moment of illusion” (Lord Jim) as in a trompe-l’œil. The truth is also that of a metaphysical void corresponding to the epistemological break at the turn of the century and the loss of faith and ideals.